Pengaruh likuiditas, risiko kredit dan efisiensi operasional terhadap profitabilitas bank persepsi pasca kebijakan tax amnesty yang terdaftar di Bursa Efek Indonesia pada tahun 2016-2019 - Indra Tri Wahyuni; Trisni Suryarini (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the effect of liquidity, credit risk and operational efficiency on the profitability of receiving banks after the tax amnesty policy. The population in this study is the receiving banks that receives repatriation funds and ransom money for tax amnesty policy which is listed on the Indonesia Stock Exchange (IDX) in 2016-2019 with a total of 77 receiving banks. The sampling technique in this study used purposive sampling method. This results in a sample of 20 receiving banks with 66 units of analysis after reducing the outliers of 14 data. The use of data analysis methods in this study used descriptive statistical analysis and inferential statistical analysis, namely multiple regression analysis. The results showed that liquidity and credit risk had no effect on receiving bank profitability after the tax amnesty policy. Meanwhile, operational efficiency has a negative effect on received bank profitability after the tax amnesty policy. So it can be said that the operational efficiency after the tax amnesty policy is to determine the level of profitability by banks, meaning that the higher the level of bank operational efficiency, the lower the level of bank profitability